From Divine Timemaker to Divine Watchmaker: An Exploration of God's Temporality - Mullins, R. T. (Routledge Studies in Analytic and Systematic Theology Series, 2024)
This book offers the most extensive exploration of divine temporality to date, providing an up-to-date discussion of issues within analytic metaphysics, philosophy of time, and philosophy of religion, and draws on the resources of contemporary systematic, historical, and biblical theology.